Human-Wildlife Conflict around Belo-Bira Forest, Dawro Zone, Southwestern Ethiopia. (20th July 2021) - Shanko, Getahun; Tona, Bekele; Adare, Barena
Abstract : Human-wildlife conflict (HWC) is a continuous problem in the world and has a significant impact on both human and wildlife populations. This study was conducted to investigate the HWC around Belo-Bira Forest, Dawro zone, southwestern Ethiopia. We collected data from October 2019 to March 2020 through semistructured questionnaires, focus group discussion, direct observation, and key informant interviews. Our results show that crop damage and livestock predation were common problems caused by Papio anubis, Cercopithecus aethiops, Crocuta crocuta, Canis aureus, and Potamochoerus larvatus . Human population growth, habitat disturbance, proximity to natural forest, and competition between wildlife and livestock are the identified causes of HWC. Moreover, the study identified guarding and fencing as dominant traditional methods used to reduce HWC in our study area. Therefore, local communities can minimize crop loss by using the most effective method in an area, and crops such as wheat, maize, and teff should not be grown near the forest edge.